Virus y fitoplasmas en el cultivo del maiz (Zea mays, L.) en cuba. Distribucion y diagnostico - Gonzalez, G.A.=700 1 San Pedro, J.; Arencibia, N.; Ruiz, M.; Fernandez, J.; Valdes, S.; Quiala, I.
(Es, En)
Ilus., 11 ref.
Keywords: ZEA MAYS; VIRUS; FITOPLASMAS; CUBA